2015
DOI: 10.1021/ar500440b
|View full text |Cite
|
Sign up to set email alerts
|

Mesocrystals in Biominerals and Colloidal Arrays

Abstract: Mesocrystals, which originally was a term to designate superstructures of nanocrystals with a common crystallographic orientation, have now evolved to a materials concept. The discovery that many biominerals are mesocrystals generated a large research interest, and it was suggested that mesocrystals result in better mechanical performance and optical properties compared to single crystalline structures. Mesocrystalline biominerals are mainly found in spines or shells, which have to be mechanically optimized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(177 citation statements)
references
References 64 publications
4
172
1
Order By: Relevance
“…Gower and co-workers have fabricated a variety of non-equilibrium (i.e., non-faceted) morphologies of minerals by using PILP as the precursor, including crystal drops [21], thin films/tablets [62,140,141], and fibers [142,143]. With the help of polyelectrolytes, Cölfen and co-workers have made varied CaC mesocrystals (superstructured nanocrystals with a common crystallographic orientation) (see the review of mesocrystals in biominerals [144]). A mesocrystal can be obtained by the oriented attachment of crystalline precursors [16,[145][146][147].…”
Section: Biomimetic Mineralization In the Presence Of Non-matrix Protmentioning
confidence: 99%
“…Gower and co-workers have fabricated a variety of non-equilibrium (i.e., non-faceted) morphologies of minerals by using PILP as the precursor, including crystal drops [21], thin films/tablets [62,140,141], and fibers [142,143]. With the help of polyelectrolytes, Cölfen and co-workers have made varied CaC mesocrystals (superstructured nanocrystals with a common crystallographic orientation) (see the review of mesocrystals in biominerals [144]). A mesocrystal can be obtained by the oriented attachment of crystalline precursors [16,[145][146][147].…”
Section: Biomimetic Mineralization In the Presence Of Non-matrix Protmentioning
confidence: 99%
“…[37][38][39][66][67][68][69][70][71] It is likely that the already reported examples of some of the superlattices reported to be formed directly in solution are produced by a concerted growth-organization process and constitute similar cases. It has been invoked 36 that polar ligand systems inducing electrostatic interactions could promote the spontaneous formation of supercrystals during growth.…”
Section: Evolution Of Co Nanorod Superlattice Formationmentioning
confidence: 99%
“…It is observed that NFT-500 has a sheet-like structure with {0 0 1} facet dominated from the selective area electron diffusion (SAED) in Fig. 4A inset [19]. Comparable to other samples with different annealing temperatures in Table 1, the EDS analysis of NFT-500 exhibited the high concentrations of N (3.23 wt%) and F (4.87 wt%) in Fig.…”
Section: Synthesis and Structures Of Doped Tmcmentioning
confidence: 85%
“…It is inferred that the anisotropic dissolution of NH 4 TiOF 3 can chemically convert to TiO 2 mesocrystal (TMC) during the topochemical transformation, accompanying with N and F releasing [13][14][15][16]. As a new class of porous building blocks oriented assembly of nanocrystals, the obtained TMC with a well-defined crystal shape significantly enhances the charge separation with remarkably long-lived charges and exhibits excellent photocatalytic activities http compared with TiO 2 nanocrystals and commercial P25 [17][18][19][20]. It is a great of significance to introduce the dopant simultaneously from the original precursors or intermedium during the synthesis, without affecting the nucleation and growth of TMC.…”
Section: Introductionmentioning
confidence: 99%